Pengaruh Pembelajaran Daring Terhadap Karakter Rasa Ingin Tahu Siswa Kelas 5 SD Negeri 8 Sekayu: Pembelajaran Daring, Karakter, Rasa Ingin Tahu - Urbaningrum, Anisa; Ferdiansyah, M; Laksana, Robert Budi (Indonesian Research Journal on Education, 2023)
This research was motivated by changes in the learning system during the COVID-19 pandemic from direct learning to online learning. The problem in this study is that during online learning there is a change in the character of students, where during the online learning process there is less interaction between teachers and students to ask questions, and students do not listen to the material delivered by theteacher seriously. This study aims to determine whether or not there is an effect of online learning on the curiosity character of 5th graders at SD Negeri 8 Sekayu. The method used in this research is True Experimental Design. Data collection techniques using questionnaires, observation, and documentation. Based on the results of the study by looking at the results of the questionnaire and observation, it was found that there was a difference in curiosity that was not too significant between the experimental class and the control class, with the calculation of the hypothesis test t_count (0.52) < t_table (2.04) which means Ha is accepted and Ho rejected. So it can be concluded that the previous provisional hypothesis shows that "there is no effect of online learning on the curiosity character of 5th graders of SD Negeri 8 Sekayu”.